2010
DOI: 10.1002/ajmg.a.32909
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling update

Abstract: In vertebrate hedgehog signaling, hedgehog ligands are processed to become bilipidated and then multimerize, which allows them to leave the signaling cell via Dispatched 1 and become transported via glypicans and megalin to the responding cells. Hedgehog then interacts with a complex of Patched 1 and Cdo/Boc, which activates endocytic Smoothened to the cilium. Patched 1 regulates the activity of Smoothened (1) via Vitamin D3, which inhibits Smoothened in the absence of hedgehog ligand or (2) via oxysterols, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 267 publications
(416 reference statements)
1
86
0
4
Order By: Relevance
“…( Figure 1) (10). The in vivo relevance of the induction of these genes was proven in ischemia experiments, in which intramyocardial gene transfer of SHH promoted recovery and preservation of left ventricular function in myocardial ischemia by enhanced neovascularization (11), supporting the notion that HH aids in ischemic tissue rescue and especially in its revascularization.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…( Figure 1) (10). The in vivo relevance of the induction of these genes was proven in ischemia experiments, in which intramyocardial gene transfer of SHH promoted recovery and preservation of left ventricular function in myocardial ischemia by enhanced neovascularization (11), supporting the notion that HH aids in ischemic tissue rescue and especially in its revascularization.…”
Section: Introductionmentioning
confidence: 74%
“…Under HH-unligated conditions, PTCH1 keeps a second transmembrane receptor called Smoothened (SMO) inactive (9). In mammals, this probably involves translocation of a vitamin D3-like 3-β hydroxysteroid (10 ates signaling through the gliomaassociated (GLI) transcription factors, resulting in the transcription of target genes, including both GLI1 and PTCH1…”
Section: Introductionmentioning
confidence: 99%
“…2 Interestingly, Guy and colleagues 1 observed a significant correlation between nuclear accumulation of GLI2, liver fibrosis, and other risk factors for NAFLD. Accordingly, we found that GLI2 was overexpressed in liver extracts from rats treated with high fat/high fructose (HF/HFr) diet as compared with standard diet (Fig.…”
Section: To the Editormentioning
confidence: 99%
“…After Hh binding, PTCH1 is internalized and degraded, allowing Smo to translocate to the cell membrane where it initiates a downstream signalling responsible for the release of the glioma-associated (Gli) proteins from the inhibitor complex Suppressor of Fused (SUFU). The subsequent activation and nuclear translocation of Gli transcriptional factors results in increased expression of genes encoding for growth factors, cell cycle regulators, cell adhesion molecules, matrix proteins, other transcription factors, and inhibitors of the Hh pathway itself (Cohen, 2010;Ruiz i Altaba et al, 2002).…”
Section: The Hedgehog Pathwaymentioning
confidence: 99%